The Importance of Understanding Emotional Regulation Strategies in Children with Autism Spectrum Disorder - Maya Zaina Billah; Nina Demia Sitepu; Meksi Barno Meliano Akailupa; Melda Rumia Rosmery Simorangkir (PERFECT EDUCATION FAIRY, 2026)
Children with Autism Spectrum Disorder (ASD) frequently experience difficulties in recognizing, expressing, and regulating their emotions, which significantly affects their social interaction and communication skills. This study aims to examine the importance of understanding appropriate emotional regulation strategies to support children with ASD in their socio-emotional development. The method employed in this research is a systematic literature review of relevant empirical studies and scholarly articles. The findings indicate that appropriate emotional regulation interventions contribute substantially to improving communication skills, social interaction, and adaptive behavior among children with ASD. Strategies such as visual schedules, positive reinforcement, occupational therapy, social stories, and sensory-based interventions have been shown to assist children in identifying and expressing emotions in a constructive manner. Furthermore, consistent emotional support from parents, educators, and caregivers plays a critical role in fostering optimal socio-emotional development. The study highlights that emotional regulation constitutes a foundational life skill that enhances social competence, academic engagement, independence, and overall quality of life for children with ASD.